Walking an EmotionalTightrope: Examining the Carceral Emotion Culture(s) of Federal Prisons for Women in Canada - Fayter, Rachel (The prison journal, 2024)
This article examines the role of solidarity as a centrally distinguishing feature of two distinct emotion culture(s) operating in federal prisons for women in Canada. We explore the social interactions between correctional officers and inmates and among criminalized women to understand how group cohesion is shaped by the power dynamics between these groups in the prison environment. For correctional officers, solidarity facilitates difficult aspects of their work and enables them to behave antagonistically towards inmates. Despite prison staff's efforts to disrupt prisoner solidarity, solidarity serves two key functions for criminalized women–emotional coping and resistance to systemic oppression.